"Distribution According to Work": An Historical Analysis of the Incentive System in China's State-Owned Sector. (June 2018) - Qi, Hao
This article analyzes the role of the incentive system in driving China's economic transition. The reform of the incentive system during the late 1970s and early 1980s led to the abuse of material incentives. Changes in the incentive system led to recurrent inflation and squeezed profits. The state thus launched a series of reforms that commoditized labor power and divided cadres from workers, substantially weakening workers' power and promoting China's economic transition.